Musculoskeletal disorders among operators of visual display terminal - Ong, C. N.; Chia, S. E.; Jeyaratnam, J.; Tan, K. C. (Scandinavian Journal of Work, Environment & Health, 1995)
Using a visual display terminal (VDT) is today a common occupational task with both benefits and hazards. One of the hazards is the occurrence of musculoskeletal disorders. This paper examines the possible causes of such disorders and suggests some preventive strategies. The debate on the relationship between musculoskeletal disorders and VDT usage usually centers around occupational factors (eg, constrained posture, poor ergonomic design of the workplace, equipment design), work-related psychological factors (eg, perceived high job demands, mundane, boring and repetitive job activity, little control, poor support from colleagues and superiors), and psychosocial factors (eg, biodemographic characteristics such as age, previous musculoskeletal injuries, emotional stress, family burden, environmental factors). Improving the ergonomic design of VDT workstations, changing occupational legislation, and improving occupational health services have been suggested as means to decrease the incidence of musculoskeletal disorders among VDT workers. Much research with a multidisciplinary approach is still needed.